Peningkatan Pengetahuan Ibu Tentang Kekurangan Energi Kronik (KEK) dan Gizi pada Ibu Hamil - Kurniati Akhfar; Jusni; Rahmaniyah. R; Irma Suryani Saleh (JCS, 2024)
Chronic energy deficiency (CED) occurs in people who suffer from protein and energy deficiencies during pregnancy. Based on data from the World Health Organization, it is currently estimated that there are 32 million pregnant women worldwide experiencing nutritional problems, meanwhile, the prevalence of CED pregnant women in Indonesia is currently quite high. The impact of Chronic Energy Deficiency (CED) on mothers causes the risk of complications such as anemia, bleeding, complications of childbirth, and fatigue, various factors that can cause CED problems in pregnant women include the lack of knowledge of pregnant women about CED. Due to the lack of knowledge about the nutrition of pregnant women, it can result in a lack of nutritious food during pregnancy. This problem is the background for community service activities regarding counseling on chronic energy and nutritional deficiencies in pregnant women with the aim of this mentoring service to increase mothers' knowledge about chronic energy and nutritional deficiencies in pregnant women. The method with communicative information techniques and using 3 approaches, namely observation, counseling and evaluation, the target in this activity is 17 pregnant women. The results showed that before being given counseling, only 4 people (24%) had good knowledge, after being given counseling, the category of good knowledge increased to 13 people (81%). So it can be concluded that there was an increase in the knowledge of pregnant women about KEK before and after being given counseling.